Workspace zone differentiation and visualization for virtual humans - Yang, J.; Sinokrot, T.; Abdel-Malek, K.; Beck, S.; Nebel, K. (Ergonomics, 2008)
Human performance measures such as discomfort and joint displacement play an important role in product design. The virtual human Santos™, a new generation of virtual humans developed at the University of Iowa, goes directly to the computer-aided design model to evaluate a design, saving time and money. This paper presents an optimization-based workspace zone differentiation and visualization. Around the workspace of virtual humans, a volume is discretized to small zones and the posture prediction on each central point of the zone will determine whether the points are outside the workspace as well as the values of different objective functions. Visualization of zone differentiation is accomplished by showing different colours based on values of human performance measures on points that are located inside the workspace. The proposed method can subsequently help ergonomic design. For example, in a vehicle's interior, the controls should not only lie inside the workspace, but also in the zone that encloses the most comfortable points. Using the palette of colours inside the workspace as a visual guide, a designer can obtain a reading of the discomfort level of product users.